FRET in Membrane Biophysics: An Overview - Loura, Luís M. S. (2011)
Förster resonance energy transfer (FRET), in most applications used as a "spectroscopic ruler," allows an easy determination of the donor-acceptor intermolecular distance. However, the situation becomes complex in membranes, since around each donor there is an ensemble of acceptors at non-correlated distances. In this review, state-of-the-art methodologies for this situation are presented, usually involving time-resolved data and model fitting. This powerful approach can be used to study the occurrence of phase separation ("rafts" or other type of domains), allowing their detection as well as size evaluation. Formalisms for studying lipid-protein and protein-protein interactions according to specific topologies are also addressed. The advantages and added complexity of a specific type of FRET (energy homotransfer or energy migration) are described, as well as applications of FRET under the microscope.